2009
DOI: 10.5551/jat.no414
|View full text |Cite
|
Sign up to set email alerts
|

Serum Gamma-Glutamyl Transferase Levels are Associated with Metabolic Syndrome in Community-Dwelling Individuals

Abstract: Aim: Serum gamma-glutamyl transferase (GGT) activity changes in response to oxidative stress. Metabolic syndrome (MetS) is associated with an increased risk of major cardiovascular events. Few data are available on the association between serum GGT and the prevalence of MetS among community-dwelling individuals in Japan. Methods: We recruited 793 men (mean age, 60 14 years), and 1,073 women (62 12 years), free from any history relating to cardiovascular disease during their annual health examination, from a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 31 publications
4
28
0
Order By: Relevance
“…The results suggest a strong correlation between GGT and MetS. Previous studies have shown that serum GGT is associated with MetS and its characteristic components in both genders 15,25) . Although the detailed mechanism underlying the relationship between GGT levels and MetS is not completely understood, hepatic insulin resistance may be involved [26][27][28] .…”
Section: Discussionsupporting
confidence: 55%
“…The results suggest a strong correlation between GGT and MetS. Previous studies have shown that serum GGT is associated with MetS and its characteristic components in both genders 15,25) . Although the detailed mechanism underlying the relationship between GGT levels and MetS is not completely understood, hepatic insulin resistance may be involved [26][27][28] .…”
Section: Discussionsupporting
confidence: 55%
“…Hepatocyte accumulation of esterified fatty acids constitutes a stressful stimulus that result in mitochondrial dysfunction with increased ROS production [28], and therefore becoming a crucial situation for liver injury that can be identified by serum γ -GT alterations. Elevations in γ -GT concentrations is also used to identify chronic alcohol consumption and is related to inflammatory markers [29], blood glucose [30], and metabolic syndrome [31]. In addition, elevations of γ -GT concentrations could be an indirect marker of antioxidant response to increased ROS production once γ -GT acts on the glutathione metabolism by regulating the oxidized glutathione clearance [32].…”
Section: Discussionmentioning
confidence: 99%
“…Several population-based investigations have noted relatively independent cross-sectional and prospective associations between serum GGT levels and certain cardiovascular risk factors [8][9][10][11][12][13][14][15][16] . Most of these studies refer to 'normal' serum GGT levels, which would otherwise raise no specific health concern.…”
Section: Landmark Clinical Trialsmentioning
confidence: 99%
“…Even more recently, Emdin et al reported the additive prognostic value of GGT in CAD along with C-reactive protein (CRP), an acute-phase reactant of hepatic origin and a sensitive marker for systemic inflammation, and fasting glucose 13) . Kawamoto et al performed a cross-sectional study to examine whether serum GGT was associated with the prevalence of metabolic syndrome among community-dwelling individuals in Japan 14) . The authors recruited 793 men (mean age, 60 14 years), and 1,073 women (mean age, 62 12 years), free from any history relating to CVD during their annual health examination, from a single community.…”
Section: Landmark Clinical Trialsmentioning
confidence: 99%